2004
DOI: 10.1051/vetres:2004012
|View full text |Cite
|
Sign up to set email alerts
|

Pathophysiological changes occurring duringEscherichia coliendotoxin andPasteurella multocidachallenge in piglets: relationship with cough and temperature and predicitive value for intensity of lesions

Abstract: -The aims of this study were (1) to correlate cough and body temperature (BT) with the severity of bronchopneumonia in pigs, (2) to determine whether these clinical signs can be used to early diagnose bronchopneumonia and (3) to assess the predictive values of cough and BT regarding lung lesions. Bronchopneumonia was induced by administering E. coli endotoxin (LPS) combined with Pasteurella multocida type A (PmA) in the trachea of 13 piglets. Saline-instilled negative controls (n = 8), PmA inoculated (n = 6) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 19 publications
(25 reference statements)
0
19
0
Order By: Relevance
“…Differences between studies may be related to the animal species used, level and type of oils used and immune status of the animal under study. The immunological challenge resulted in the poor performance of animals (Benson et al, 1993;Klasing and Korver, 1997;Halloy et al, 2004), which was attributed to the partitioning of nutrients away from growth and toward processes associated with inflammatory immune responses in chickens . Some studies indicated that these changes are attributed to the release of proinflammatory cytokines (Johnson, 1997;Webel et al, 1997;Sijben et al, 2001), including TNF, IL-1 and IL-6.…”
Section: Discussionmentioning
confidence: 99%
“…Differences between studies may be related to the animal species used, level and type of oils used and immune status of the animal under study. The immunological challenge resulted in the poor performance of animals (Benson et al, 1993;Klasing and Korver, 1997;Halloy et al, 2004), which was attributed to the partitioning of nutrients away from growth and toward processes associated with inflammatory immune responses in chickens . Some studies indicated that these changes are attributed to the release of proinflammatory cytokines (Johnson, 1997;Webel et al, 1997;Sijben et al, 2001), including TNF, IL-1 and IL-6.…”
Section: Discussionmentioning
confidence: 99%
“…Despite extensive studies in mice with this method, controversy exists regarding Penh and whether it represents a valid measure of bronchoconstriction in mice (19). However, Halloy et al (90,91) have shown in swine that airway reactivity measurements made with WBBP correlate well with esophageal balloon-pneumotachograph measurements following acetylcholine and endotoxin challenge and have also tested WBBP after pulmonary challenge with P. multocida.…”
Section: Whole Body Barometric Plethysmographymentioning
confidence: 99%
“…Fever is the earliest and one of the main clinical signs of many diseases (Plonait, 2004). Previous investigations showed that S. typhimurium challenged piglets showed increased body temperature (Balaji et al, 2000), while E. coli endotoxin inoculation resulted in subnormal body temperature (Halloy et al, 2004) compared to controls. Based on the way heat is transmitted through the skin of swine, infrared images have the potential for use in the detection of body temperature (Ingram and Weaver, 1969;Godynicki et al, 1985).…”
Section: Introductionmentioning
confidence: 97%